Exploration of acupuncture therapy in the treatment of MCI patients with the ApoE ε4 gene based on the brain-gut axis theory - Yuanyuan Jin; Jin Chen; Qichen Chai; Jianfang Zhu; Xiaoqing Jin (BMC, 2023)
Abstract Background Mild cognitive impairment (MCI) is the predementia phase of Alzheimer's disease (AD). The intestinal microbiome is altered in MCI and AD, and apolipoprotein E (ApoE) ε4 gene polymorphism is a risk factor for the progression of MCI to AD. This study aims to investigate the improvement in cognitive function of MCI patients with and without ApoE ε4 due to acupuncture and the changes in gut microbiota community composition and abundance in MCI. Methods This randomized assessor-blind controlled study will enrol MCI patients with and without the ApoE ε4 gene (n = 60/60). Sixty subjects with the ApoE ε4 gene and 60 subjects without the ApoE ε4 gene will be randomly allocated into treatment and control groups in a 1:1 ratio. Intestinal microbiome profiles will be evaluated by 16 S rRNA sequencing of faecal samples and compared between the groups. Results/conclusions Acupuncture is an effective method to improve cognitive function in MCI. This study will provide data on the relationship between the gut microbiota and the effectiveness of acupuncture in patients with MCI from a new angle. This study will also provide data on the relationship between the gut microbiota and an AD susceptibility gene by integrating microbiologic and molecular approaches. Trial registration www.chictr.org.cn , ID: ChiCTR2100043017, recorded on 4 February 2021.